The Causes and Solutions of Moral Decline in the Quran - Yahyazadeh, Nijat (Scholarya Demo Journal of Ruby, 2024)
People naturally strive for perfection, but achieving this goal requires dedication and effort. A person’s healthy moral and behavioral foundation is essential for reaching the highest peak of perfection. As a social being, it is crucial to maintain control over one’s morals and behavior to interact with others in a respectful manner. The Quran provides a comprehensive guide to morality and behavior, emphasizing the essential principles for a person’s personal and social life.The Quran places great value on the subject of morality, offering a profound perspective on its significance. To convey the gravity of this topic, the Quran identifies the factors that lead to moral decline as well as the solutions to overcome these problems. According to Quranic verses, selfish desires, heedlessness, suspicion and greed are listed as causes of moral decline. On the other hand, believing in God wholeheartedly, avoiding sin, fearing divine punishment and doing justice are presented as solutions to overcome moral decay.This article employs a descriptive-analytical approach to study and analyze the causes of moral decline and their solutions from a Quranic perspective, using religious texts as a basis for content analysis. This interdisciplinary study combines topics from morality, law, sociology and the Quran, reflecting a widely accepted method of thematic interpretation in modern times.